A short synthesis of aphanamol I in both racemic and enantiopure forms - Burton, J; Ferrara, S (Wiley, 2016)
A short synthesis of the biologically active sesquiterpene natural product (+)-aphanamol I in both racemic and enantiopure forms is reported. Key steps include: a catalytic enantioselective conjugate addition, an oxidative radical cyclisation, and a ringexpanding Claisen rearrangement.